2018
DOI: 10.1155/2018/5459307
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction of Collinear Cracks and Wing Cracks and Cracking Behavior of Rock under Uniaxial Compression

Abstract: is paper investigates the crack interaction, initiation, and propagation rules of rock-like materials containing two collinear cracks. Based on the Kachanov method, the formulations for stress intensity factors (SIFs) of two collinear cracks and two winged cracks are derived, respectively. e influences of bridge ligament and crack length on the crack interaction are analyzed theoretically. e results show that the propagation of a long crack is independent of crack interaction when d ≥ a 2 and the same rule app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In order to ensure the smooth excavation of the tunnel, the full-section curtain grouting method is used to block water and reinforce the tunnel. 4 Geofluids igneous orientation arrangement. According to the survey data, the rocks are divided into four weathering layers, namely, total weathering, strong weathering, moderate weathering, and breeze weathering, which are mainly composed of variable granitic structure, scaly crystalline structure, and block-shaped and gin-shaped structure.…”
Section: Engineering Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure the smooth excavation of the tunnel, the full-section curtain grouting method is used to block water and reinforce the tunnel. 4 Geofluids igneous orientation arrangement. According to the survey data, the rocks are divided into four weathering layers, namely, total weathering, strong weathering, moderate weathering, and breeze weathering, which are mainly composed of variable granitic structure, scaly crystalline structure, and block-shaped and gin-shaped structure.…”
Section: Engineering Backgroundmentioning
confidence: 99%
“…In the process of tunnel excavation, water and mud inrush often occurs [1][2][3]. Although people have made considerable progress in understanding the mechanical properties of rock mass [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and theories and technologies of tunnel excavation and support have been greatly developed [21][22][23][24][25], it still cannot completely contain the occurrence of water and mud inrush. Every year, water and mud inrush still causes a large number of equipment losses and casualties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rock damage induced by blasting load can be divided into compression damage and tension damage. Meanwhile, rock is more sensitive to tensile stress because of the lower tensile strength of rock [31][32][33]. Thus, rock mainly showed as tension damage and many tension cracks will appear result in rock fragmentation under dynamic load [34][35][36][37].…”
Section: Materials Modelsmentioning
confidence: 99%
“…The results showed that the filling material can reduce the tip stress. Wang [26] studied the crack interaction, initiation and propagation of rock-like materials with two collinear fissures. The results showed that with the growth of wing cracks, the stress intensity factor of wing cracks first decreases and then tends to be stable.…”
Section: Introductionmentioning
confidence: 99%